STRATEGI INDONESIA DALAM PENCALONAN DEWAN INTERNATIONAL TELECOMMUNICATION UNION (ITU) DALAM PLENIPOTENTIARY (PP) TAHUN 2022 - Reyhan Fawarizki Darman; Umi Oktyari Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
International Telecommunication Union (ITU), is the oldest inter-governmental organization that was founded in 1865. ITU is a specialized agency under the United Nations (UN). ITU has a council that acts as the union’s governing body in the interval between Plenipotentiary (PP) conferences that held every five years. ITU is one of the important UN Specialized Agency, thus, being a member of ITU council will bring high credibility to Indonesia in the field of Information and Communication Technology (ICT). In PP ITU 2022 that held on September 26th to October 14th, reported that Indonesia has claimed a seat in ITU Council for 2023-2026 period. The purpose of this research is to find out the strategy of Indonesia in winning a seat in ITU Council for the 2023-2026 period. This study used a liberalism perspective, with a country analysis level. This study also uses multitrack diplomacy theory. The method used in this study is a qualitative method with data collection techniques using literature and various literature that refers to books, journals, sites on the internet combined with interview to one of Indonesia’s delegation in ITU PP 2022. The results of study show that Indonesia used the first and ninth track of multitrack diplomacy. The first track was carried out with various diplomatic activities, such as bilateral, regional, multilateral meetings, diplomatic reception, and intensive lobbies during PP ITU. The ninth track was carried out by using the mass media in distributing Indonesia’s efforts on being selected as one of the council. This strategy achieved Indonesia’s success in getting a seat on the ITU Council for the 2023-2026 period. Keywords: Diplomacy, ITU, Plenipotentiary, ITU Council